(untitled) (Journal of Nuclear Technology in Applied Science, 2019)
Over the past several decades, people have been constantly exposed to electric and magnetic fields from both industrial and domestic uses. The present study was designed to investigate the possible protective effect of garlic aqueous extract on oxidative stress, neurotransmitters and histological changes in the brain of male albino rats exposed to extremely electromagnetic fields (EMFs). In this experimental study, Forty male albino rats were divided into four equal groups: control; garlic (500 mg/Kg b.w); irradiated (exposed to the 950MHz electromagnetic field for one hour); garlic-irradiated (received garlic extract half an hour before EMF exposure). The garlic extract administration and EMF exposure were three times per week (day after day) for 7 weeks. The result of the present study showed that exposure to EMF provoked oxidative stress in the brain tissues notified by significant decreases of reduced glutathione (GSH) content associated with significant increase levels of malondialdehyde (MDA) and nitric oxide (NO). Alteration of neurotransmitters was verified by significant decreases in the levels of dopamine (DA), norepinephrine (NE), and serotonin (SE). These alterations were associated with histological changes and deposition of B-amyloid in the brain cerebral cortex. Garlic administration significantly attenuated the brain biochemical disturbances and histological changes of the EMF exposed rats. According to the result obtained in the present study it could be concluded that exposure to EMF can cause biochemical and histological damage, and garlic can diminished these alterations, throughout enhancing the endogenous antioxidant defenses